2017
DOI: 10.12783/dtmse/amsee2017/14305
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Impact of Urbanization on the Living Energy Consumption of Residents in China

Abstract: Abstract. In order to explore the impact of urbanization on the consumption of living energy, this paper conducts an in-depth study on the living energy consumption structure and consumption of urban and rural areas respectively. First, collect 2001-2014 of urban and rural household energy consumption of all types of data, using the partial least squares method to analyze the urban and rural living energy consumption structure respectively, and carrying out the Zou test on the regression results. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Concerning the decomposition results, technology effect and industrial structure played a major role in decoupling between WEF resources use and economic growth, while economic scale contributed most to the increase in WEF consumption. This is in line with some previous studies exploring the factors influencing the decoupling of water [29,76], energy [31,44], and food consumption [35]. The results showed that the industrial structure factor had a greater impact on the decoupling in 2015-2017 than in 2012-2015, especially in terms of energy consumption.…”
Section: Factors Influencing the Sustainable Development Of The Yangt...supporting
confidence: 91%
See 1 more Smart Citation
“…Concerning the decomposition results, technology effect and industrial structure played a major role in decoupling between WEF resources use and economic growth, while economic scale contributed most to the increase in WEF consumption. This is in line with some previous studies exploring the factors influencing the decoupling of water [29,76], energy [31,44], and food consumption [35]. The results showed that the industrial structure factor had a greater impact on the decoupling in 2015-2017 than in 2012-2015, especially in terms of energy consumption.…”
Section: Factors Influencing the Sustainable Development Of The Yangt...supporting
confidence: 91%
“…As China's economic growth is transforming from an extensive mode to a sustainable and green development one, it is necessary to decouple economic growth from resource utilization so that ecological degradation can be mitigated. Most studies focused on singleresource decoupling, such as via water [26][27][28][29], energy [30,31], carbon emissions [32][33][34], and food [35][36][37]. A few studies have attempted to explore the decoupling states between economic growth and multiple resource utilization.…”
Section: Of 21mentioning
confidence: 99%